The SOCIAL CAPITAL, LEADERSHIP, AND FOREST PARTICIPATION ACROSS ELEVATION GRADIENTS IN UPPER BENGAWAN SOLO - Dwi Apriyanto Apriyanto; Bramasto Nugroho; Leti Sundawati; Joko Sutrisno (Forestry Study Program University Of Mataram, 2026)
The Upper Bengawan Solo Watershed is one of Indonesia’s priority river basins and faces severe land degradation, much of which occurs on privately owned smallholder land. Private forests have become an important strategy for land rehabilitation, yet farmers’ participation in forest management remains uneven. This study examines the roles of social capital, local leadership (symbolic power), and shared knowledge in shaping participation in private forest management across elevation strata in Wonogiri Regency, Indonesia. A quantitative survey was conducted with 210 private forest farmers, and data were analyzed using the Kruskal–Wallis test and multiple linear regression. The results show significant differences in trust, shared knowledge, and the overall social capital index across elevation strata. However, the effects of social capital dimensions on participation are inconsistent. In contrast, symbolic power (β = 0.221, p < 0.05) and shared knowledge (β = 0.198, p < 0.05) positively and significantly influence participation, emerging as stronger predictors than trust, networks, and norms. Elevation strata are not significantly associated with participation, indicating that ecological conditions serve primarily as a socio-ecological context rather than direct drivers of collective action. These findings suggest that social capital alone is insufficient to promote participation unless activated through legitimate local leadership and shared understanding among farmers. Strengthening local leadership and collaborative learning processes may therefore enhance participation and support sustainable private forest management.